Novel cyclic undecapeptides immobilized on reduced graphene oxide surface for enhanced antibacterial properties - Farrag, H. N.; Zheng, A. L. T.; Sabidi, S.; Wu, Y.; Ikeno, S.; Maeda, T.; Andou, Y.; Kato, T. (Springer, 2023)
The incorporation of antimicrobial peptides (AMPs) in graphene-based materials is a growing strategy to overcome the shortcomings presented by conventional antimicrobial nanomaterials derived from metal/metal oxide. In this study, novel cyclic undecapeptides CH1 and CW2 (KRQRFYFRQRK and QNKRFYFRKNQ, respectively) were successfully synthesized. The cyclic peptides were then immobilized on the reduced graphene oxide (rGO) surface using a water-soluble carbodiimide (EDCI/HCl) linker. The structural, morphology, and chemical characterizations of the antimicrobial graphene material were carried out using SEM, Raman, FTIR, XRD, and XPS. From our result, the peptide/rGO composite showed an improved antibacterial effect towards gram-positive (Staphylococcus aureus) and gram-negative (Pseudomonas aeruginosa). The enhanced antibacterial property is attributed to the synergistic effect of the sharp edges of rGO and the amphipathic moieties of the cyclic peptides.